Curating live arts : critical perspectives, essays, and conversations on theory and practice - Davida, Dena; Gabriels, Jane; Hudon, Véronique; Pronovost, Marc (Berghahn Books, 2019)
"Situated at the crossroads of performance practice, museology, and cultural studies, live arts curation has grown in recent years to become a vibrant interdisciplinary project and a genuine global phenomenon. Curating Live Arts brings together bold and innovative essays from an international group of theorist-practitioners to pose vital questions, propose future visions, and survey the landscape of this rapidly evolving discipline. Reflecting the field's characteristic eclecticism, the writings assembled here offer practical and insightful investigations into the curation of theatre, dance, sound art, music, and other performance forms--not only in museums, but in community, site-specific, and time-based contexts, placing it at the forefront of contemporary dialogue and discourse"-- Provided by publisher
Keywords: Performing arts archives.; Archives des arts du spectacle.; SPORTS & RECREATION / General.; PERFORMING ARTS / General; Performing arts archives; Curatorship; Performing arts